PSYCHOANALYSIS OF RILEY CHARACTER IN THE DISNEY MOVIE “INSIDE OUT” - Sistha, Cantika Widya; Nur, Riola Haya; Fitriyani, Fitriyani (Journal of English Literature and Linguistic Studies, 2023)
This study intends to look into the psychological traits that Riley, Joy, and Sadness—the three main characters from the film "Inside Out"—faced. The researcher also intends to look into the reasons behind the psychological issues that the three main characters overcome as well as how they do so. Researchers employ a qualitative descriptive methodology in this strategy. The researcher examined the inherent elements to find solutions to the issues brought on by the psychological character conflicts of the "Inside Out" movie's key protagonists.